FAKTOR-FAKTOR YANG MEMENGARUHI PROCUREMENT FRAUD: SEBUAH KAJIAN DARI PERSPEKTIF PERSEPSIAN AUDITOR EKSTERNAL - Zulaikha, Zulaikha; Hadiprajitno, Paulus Basuki (Jurnal Akuntansi dan Keuangan Indonesia, 2016)
This study examines factors affecting fraud in the procurement of government’s goods and services from the independent auditor’s point of view. Based on fraud triangles and theory of planned behavior, this study proposes seven hypotheses which were tested using structural equation model (SEM)-partial least square. This study used primary data gathered by survey to auditors of Audit Board of the Republic of Indonesia in its head office and several selected representative offices. Respondents were asked to provide their answer/perception for questions in questionnaire regarding factors influencing the procurement fraud of government’s goods and services. The results show that the procurement frauds are significantly influenced by weaknesses in procurement system, lack of procurement committee’s quality, and the intention to engage fraud. Furthermore, the intention to engage fraud are influenced by attitude, subjective norms, and the perceived behavioral control. These findings suggest that procurement frauds are associated with individual factors as rationalization and opportunities. These factors could be considered when designing internal control structure to restrain fraud behavior.